Embedded Librarianship in a Unique Setting: Hospital-Based Whole-Person Health Research. Issue 1 (2nd January 2019) - Harris, Stephanie L.
ABSTRACT: Embedded librarians continue to expand their professional purview into new and challenging settings. This article explores embedded librarianship in a unique setting: a hospital-based research department focused on the science behind mind/body/spirit (i.e., whole-person) health. The inception of the role, its growth and development, and demands and opportunities reflect trends in embedded research librarianship as a whole. This position profile may serve as a model for future embedded librarian roles in nontraditional research settings.